Evaluation of Growth and Yield of Selected Hybrid and Inbred Rice (Oryza sativa L) Varieties Grown in Boro Season (The Agriculturists, 2010)
Pot experiments were conducted in net house during Boro 2002 and 2003 at Bangladesh Rice Research Institute (BRRI) to compare the growth and yield of hybrid and inbred rice varieties under controlled condition. Hybrid variety Sonarbangla-1 and BRRI hybrid dhan1 and inbred modern variety BRRI dhan29 were used in both the years. During Boro 2002, Sonarbangla-1 and BRRI hybrid dhan1 had higher plant height and tillers hill-1 compared to BRRI dhan29. The largest leaf area of 75cm2 hill-1 was recorded in BRRI hybrid dhan1 at 30 DAT but at 60 and 90 DAT, Sonarbangla-1 had the highest leaf area of 723 and 1406 cm2 hill-1, respectively. The highest shoot dry matter production was recorded in BRRI hybrid dhan1 at 30 DAT but in Sonarbangla-1 at 60 and 90 DAT. Rooting depth and root dry weight of Sonarbangla-1 were 15- 20% higher than those of BRRI hybrid dhan1 and BRRI dhan29. At harvest, the largest number of panicles hill-1 was observed in BRRI dhan29 followed by Sonarbangla-1. The number of grains panicle-1, 1000-grain weight and grain yield were higher in Sonarbangla-1 followed by BRRI dhan29. During Boro 2003, highest plant height, number of tillers hill-1, leaf area and shoot dry matter were recorded in BRRI hybrid dhan1 at all DAT, followed by Sonarbangla-1 in most cases. Rooting depth and root dry weight were the highest in Sonarbangla-1 followed by BRRI hybrid dhan1. At harvest, highest number of panicles hill-1 were observed in BRRI dhan29 and Sonarbangla-1 but BRRI hybrid dhan1 had the highest number of grains panicle-1. Sonarbangla-1 had the highest 1000-grain weight and grain yield.